STUDENT'S ATTITUDE ON USE OF ICT IN TEACHING KISWAHILI PLAY IN SECONDARY SCHOOLS IN UASIN GISHU COUNTY, KENYA. - Naumi Chepkemoi (IJRDO- Journal of Educational Research, 2019)
This study aimed at to examine the student's attitude on use of ICT in teaching and learning Kiswahili play in secondary schools. The study used social learning theory by Bandura and the functionalism theory by John Dewey. Stratified sampling and simple random sampling was applied to select 275 students from a total of 918 from form three students in Eldoret West district representing 30% of the study population. The study revealed that student's attitude on the use of ICT in teaching and learning Kiswahili play was a positive however,  students indicated that they rarely use ICT in learning Kiswahili plays and others have never used any form of ICT during their learning of Kiswahili plays. They also felt that the use of ICT is interesting during teaching and learning of Kiswahili plays. The students also agreed that by seeing they can remember more than just writing notes down, and ICT improves there thinking and creativity in them and also ease the learning as well as reducing boredom and sleep in class during Kiswahili play lessons. Therefore, there is need for Kiswahili play teachers to embrace and fully adopt use of ICT in their teaching and learning activities in secondary schools in order to enjoy the benefits of ICT in schools and to meet the national goals of education and vision 2030.